Aural and Visual Detection of Greater Sage‐Grouse Leks: Implications for Population Trend Estimates. Issue 3 (19th January 2021) - Riley, Ian P.; Conway, Courtney J.; Stevens, Bryan S.; Roberts, Shane B.
ABSTRACT: Counts of greater sage‐grouse ( Centrocercus urophasianus ) at leks have been used in harvest management, Endangered Species Act listing decisions, and land management policies for over half a century. Lek count sampling methods focus on counting male sage‐grouse at known leks, primarily those observed visually from roads or vantage points, but leks are likely missed that are unknown prior to the survey and are difficult to detect while driving between known lek sites. One way to ameliorate this shortfall may be to conduct short point‐count surveys at multiple stops along lek‐survey routes or while driving between lek counts, thereby detecting newly established or unknown leks. To evaluate the feasibility of this approach, we estimated aural and visual detection probability of active sage‐grouse leks during 1‐minute point‐count surveys at known distances and examined the effects of environmental factors on aural lek detection in southern Idaho, USA, 2016–2017. Our results demonstrate that field observers can aurally detect sage‐grouse leks at approximately 3 times greater distances compared to detecting leks visually. The probability of hearing an active lek was highest near the peak of male and female attendance (8 Apr), within an hour of sunrise, on relatively calm and cold days, when the observer was at a higher elevation relative to the lek, and during conditions with no background noise. Detection probability declined with distance and the probability of aural detection was 0.59 at 1 km from a lek when other variables were held at their means. Hence, conducting ≥3 1‐minute surveys along a lek route would be expected to detect ≥93% of all leks within 1.5 km of each survey under the average environmental conditions in our study. Our results suggest that surveys could greatly improve detection of unknown or newly established leks and can facilitate a more accurate assessment of sage‐grouse population trends through lek counts. Moreover, our results demonstrate how environmental factors influence the detection of leks during surveys, and therefore which variables should be considered for inclusion in any future revisions of lek count protocols or in analyses of lek count data. © 2021 The Wildlife Society. Abstract : We compared visual and aural detection distance during 1‐minute point‐count surveys at varying distances for active greater sage‐grouse leks in southern Idaho, USA, 2016–2017, and documented factors that influence aural detection of leks. Our results suggest current sage‐grouse lek survey methods could be slightly modified to include 1‐minute stops to provide a formalized road‐based lek survey framework to improve the detection of unknown or newly established leks within a specified area to obtain a more representative sample of leks.